Interaction of Metal Cations with Alkylnitriles in the Gas Phase: Solvation of Metal Ions by the Hydrocarbon Chain. Issue 3 (June 2015) - Jobst, Karl J.; Terlouw, Johan K.; Luider, Theo; van Huizen, Nick A.; Burgers, Peter C.
Relative affinity measurements of monovalent metal ions (M=Li +, Na +, Cu + and Ag + ) toward aliphatic nitriles have been performed using the kinetic method by dissociation of metal-bound dimer ions of the type R1 C≡N-M+-N≡CR2. It was found, particularly for Cu + and Ag +, that the affinity toward nitriles having long chains (>C6 ) is markedly enhanced. This is attributed to a bidentate interaction of the metal ion with the nitrile moiety and the aliphatic chain. Theoretical calculations on the copper complexes show that these bidentate structures enjoy about 30% greater copper-ion affinities compared to their linear counterparts. Such aliphatic interactions also play a major role in the dissociation chemistry of copper-bound tetramers of the kind (RC≡N)4 Cu 2+ where the long aliphatic chain R curls around the copper ion to facilitate electron transfer or a redox reaction to produce (RC≡N)2 Cu + + RC≡N + + RC≡N.